Pani Dalloway spotkanie ze śmiercią. O filmowej interpretacji powieści Virginii Wolf = Mrs Dalloway`s encounter with death. On the film interpretation of Virginia Wolf`s novel - Kubasiewicz, Mirosława (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The prose of Virginia Woolf poses a great challenge to film makers due to its focus on the innerlives of the characters rather than their external reality. Woolf `s portrait of the eponymous characterof "Mrs Dalloway" is not direct - she draws it obliquely, following her conviction that human life is"a luminous halo, a semi-transparent envelope" and so the full truth of it can never be gained.
Keywords: Woolf, Adeline Virginia (1882-1941); adaptacja filmowa